A characterization of the weighted Lovász number based on convex quadratic programming - Luz, Carlos J. (2016)
Luz and Schrijver (SIAM J Discrete Math 19(2):382–387, 2005) introduced a characterization of the Lovász number based on convex quadratic programming. This characterization is now extended to the weighted version of that number. In consequence, a class of graphs for which the weighted Lovász number coincides with the weighted stability number is characterized. Several examples of graphs of this class are presented.